THE POTENTIAL THREAT OF CHINA-MYANMAR GAS PIPELINE - Isnarti, Rika (AEGIS : Journal of International Relations, 2017)
China needs energy to sustain its economic growth. However the amount of energy resources in China are insufficient while the energy consumption grows rapidly. Recently, China is the second largest energy consumer. In order to achieve energy security and reduce carbon emissions to save environment, China is actively increasing the consumption of natural gas. China imports natural gas from overseas such as from Middle East, Kazakhstan, Turkmenistan and others. About half of China’s energy resources import from foreign sources. However, Import natural gas from these countries come with risks. The instability of politic in those areas influences the natural gas price, insecurity of travelling the natural gas via sea can reduce the amount natural gas come to China, and so on. China then looks alternative countries that closer to China to supply and secure its energy demand. In doing so, in 2008 China signed agreement with Myanmar to build oil gas pipeline. The gas pipelines have operated in July 2013. However, China-Myanmar gas pipelines project do not come without risk. This paper examines potential risks of China-Myanmar gas pipelines. This paper argues there are security, environmental, and cyber, and other issues that can be potential threat to China Myanmar gas pipeline project